La ciudad elimina la función agraria en su proximidad: el ejemplo de San Sebastián - Alberdi Collantes, Juan Cruz (Anales de Geografía de la Universidad Complutense, 2002)
In this paper we study the influence of the city in the periurban land of San Sebastian (Basque Country). In this area we see that the farm funtion is remove by the urban belt using different ways. The most evident of all is the urbanitation of land grow. However, before coming to the urbanitation of the rural area, the value of this grow and the space diffilcuties carry off that the farmer take the decision of leaving the farm activity.